In vitro effects of photobiomodulation therapy on 50B11 sensory neurons: evaluation of cell metabolism, oxidative stress, mitochondrial membrane potential (MMP), and capsaicin‐induced calcium flow. Issue 2 (14th November 2020) - Zupin, Luisa; Barbi, Egidio; Sagredini, Raffaella; Ottaviani, Giulia; Crovella, Sergio; Celsi, Fulvio
Abstract: The analgesic properties of photobiomodulation therapy (PBMT) have been raising increasing interest in the clinical community due to the positive effects observed on patients, nevertheless the mechanistic basis of its action on peripheral sensory neurons remains still elusive. In this study, the effect of near‐infrared (NIR) PBMT at 800 and 970 nm of wavelength was investigated on the 50B11 immortalized nociceptive sensory neuronal cell line by evaluating capsaicin‐induced calcium flow and different markers correlated to mitochondria, that is, ATP, reactive oxygen species (ROS), and mitochondrial membrane potential (MMP). Calcium peak stimulated by capsaicin, the ligand of TRPV1 channel, was decreased in neurons pre‐irradiated with the combination of the two wavelengths. Furthermore, delivering the 800 and 970 nm separately an increment of ATP, as well as MMP hyperpolarization were detected; notably, the 800 nm wavelength also increased ROS and O2 − levels. Our findings, obtained on an in vitro model of nociception, show the positive effect of PBMT on two potential photo‐targets of NIR light, namely the TRPV1 channel and the mitochondria. Abstract : The photobiomodulation therapy effects on 50B11 sensory neurons:increment of ATP, ROS, MMP and decrement of capsaicin‐induced calcium peak.